Effects of tailored interventions for anxiety management in choking-susceptible performing artists: a mixed-methods collective case study - Lubert, Veronika J.; Nordin-Bates, Sanna M.; Gröpel, Peter (Frontiers in Psychology, 2023)
Introduction Not being able to manage performance anxiety and subsequently experiencing a decline in performance have been called “choking under pressure”. High trait anxiety and fear of negative evaluation, as well as low self-efficacy or self-confidence, can put performers especially at risk of experiencing choking. This study, therefore, examined the effects of psychological choking interventions tailored to “choking-susceptible” performing artists individually in a coaching setting. Methods We conducted a mixed-methods (QUANT + QUAL) collective case study with nine performing artists, who each received five individual coaching sessions. The tailored choking interventions comprised acclimatization training, goal setting, and pre-performance routines, including elements such as imagery, self-talk, and relaxation techniques. Before and after the 10-week intervention phase, they filled in questionnaires on trait performance anxiety, fear of negative evaluation, and self-efficacy, performed in front of a jury, and were interviewed about their experiences. Transcripts of interviews and coaching sessions were analyzed using thematic analysis. Heart rate measurements, weekly performance videos, and expert evaluations were also part of our comprehensive data. Results Quantitative data showed reductions in performance anxiety and fear of negative evaluation, and increases in self-efficacy and performance quality, from before to after the intervention phase. Most participants also had a lower heart rate when performing for the jury. Themes from qualitative analysis comprised managing nervousness and feeling more relaxed, becoming more self-confident, satisfaction with artistic and mental performance, feeling good and enjoying performing, and general positive effects. Conclusion Tailoring psychological interventions may provide several benefits for choking-susceptible performing artists.